SETTLEMENT OF MEDICAL DISPUTES DUE TO MINOR OFFENCES BY HEALTH WORKERS THROUGH MEDIATION - Gunawan Widjaja (INJOSEDU: International Journal of Social and Education, 2025)
Mediation as a method of resolving medical disputes resulting from minor breaches by health workers offers an effective and efficient approach compared to litigation. The mediation process allows for an open dialogue between the patient and the health worker in a neutral setting facilitated by a mediator. It helps identify key issues and seek mutually beneficial solutions in a faster and cost-effective manner. Another advantage of mediation is that it preserves the confidentiality and reputation of both parties, and focuses on recovery and repair rather than punishment. Thus, mediation not only resolves disputes but also helps improve the relationship between patients and health workers and promotes improved quality of healthcare.